Husnuzan, Social Comparison, and Social Anxiety in Emerging Adults Social Media Users - Putri Meilani Alaska; Fuad Nashori; Muhamad Uyun (Universitas Ahmad Dahlan, 2024)
Emerging adults often use social media as a platform for exploration, but the usage is associated with various negative impacts, particularly regarding others' judgments, which can lead to social anxiety. Therefore, this study aimed to investigate the influence of husnuzan and social comparison on social anxiety among emerging adults social media users. The participants were individuals in emerging adulthood, aged 18-29 years, residing in the Special Region of Yogyakarta. Moreover, the Iowa-Netherlands Comparison Orientation Measure, Husn al-Zhan Scale, and Social Anxiety Scales for Social Media Users were used. A multiple regression analysis was carried out to explore the relationship between the three variables. The proposed hypothesis states that husnuzan and social comparison influence social anxiety. The results showed that husnuzan and social comparison significantly impacted social anxiety in emerging adults social media users, hence, optimizing husnuzan and minimizing social comparison behaviors can reduce anxiety.